Communication training and its effects on carer and care‐receiver outcomes in dementia settings: A systematic review. Issue 7 (20th November 2018) - Nguyen, Hoang; Terry, Daniel; Phan, Hoang; Vickers, James; McInerney, Fran
Abstract: Aims and objectives: To review communication interventions that aim to improve regular care interactions between people with dementia and their carers in various settings; and to examine the impact of such interventions on both carer and care‐receiver outcomes. Background: Effective communication is imperative to ensure quality of care for people living with dementia. Due to neurodegenerative changes, people with dementia encounter ongoing and progressive difficulties in both understanding and expressing themselves. This in turn creates challenges for carers, which highlights the need for equipping them with necessary communication skills to respond to the specific communication needs of people with dementia. Design: Systematic review and meta‐analysis. Method: Medline, Embase, CINAHL, ProQuest and PsycINFO databases were searched for eligible interventions with any date of the publication. Hand searching was also conducted through reviewing the reference lists of relevant articles. The screening and selection of studies were based on the inclusion/exclusion criteria for eligibility and the methodological quality assessment checklist. Random‐effects meta‐analyses were conducted on comparable quantitative data. The review is reported following the PRISMA reporting guidelines. Results: Seventeen studies were included in the final review, including 12 randomised controlled trials (RCTs), three nonrandomised controlled trials (NRCTs) and two controlled before–after interventions. The intervention designs, settings and outcome measures were varied. The findings suggest that the communication training had a positive impact on both carer and care‐receiver outcomes, albeit to different degrees. The intervention effects were found to be strongest on carer communication skills and knowledge. Conclusion: There is solid evidence for the positive impact of communication training on the skills and knowledge of carers. More research is needed regarding the effects of such educational interventions on carer physio‐psychological outcomes and care‐receiver neuropsychiatric symptoms. It is important to establish best practices in training design, develop validated outcome measures and adopt consistent reporting approaches. Relevance to clinical practice: The increasing global prevalence of people with dementia manifests across clinical and community contexts. The profound impact of dementia on communication and associated care raises the imperative for enhanced health worker and carer communication skills to meet the needs of this particular client group. The findings of this review indicate that educational interventions incorporating face‐to‐face and diverse instructional delivery methods in dementia communication showed positive outcomes for communication skills in all carer groups and warrant inclusion as strategies in dementia training.